First Detection in West Africa of a Mutation That May Contribute to Artemisinin Resistance Plasmodium falciparum - Zhao, Hui; Pi, Liang; Zhao, Luyi; Qin, Yucheng; Zeng, Weilin; Xiang, Zheng; Yang, Qi; Pan, Maohua; Li, Xinxin; Zou, Chunyan; Chen, Xi; Zhao, Wei; et al. (Frontiers in Genetics, 2021)
Background: The spread of drug resistance has seriously impacted the effective treatment of infection with the malaria parasite, Plasmodium falciparum. Continuous monitoring of molecular marker polymorphisms associated with drug resistance in parasites is essential for malaria control and elimination efforts. Our study describes mutations observed in the resistance genes Pfkelch13, Pfcrt, and Pfmdr1 in imported malaria and identifies additional potential drug resistance-associated molecular markers. Methods: Chinese patients infected in Africa with P. falciparum were treated with intravenous (IV) injections of artesunate 240–360 mg for 3–5 days while hospitalized and treated with oral dihydroartemisinin-piperaquine (DHP) for 3 days after hospital discharge. Blood samples were collected and PCR sequencing performed on genes Pfkelch13, Pfcrt, and Pfmdr1 from all isolates. Results: We analyzed a total of 225 patients from Guangxi, China with P. falciparum malaria acquired in Africa between 2016 and 2018. All patients were cured completely after treatment. The F446I mutation of the Pfkelch13 gene was detected for the first time from samples of West African P. falciparum, with a frequency of 1.0%. Five haplotypes of Pfcrt that encode residues 72–76 were found, with the wild-type CVMNK sequence predominating (80.8% of samples), suggesting that the parasites might be chloroquine sensitive. For Pfmdr1, N86Y (13.1%) and Y184F (58.8%) were the most prevalent, suggesting that artemether-lumefantrine may not, in general, be a suitable treatment for the group. Conclusions: For the first time, this study detected the F446I mutation of the Pfkelch13 gene from Africa parasites that lacked clinical evidence of resistance. This study provides the latest data for molecular marker surveillance related to antimalarial drug resistance genes Pfkelch13, Pfcrt, and Pfmdr1 imported from Africa, in Guangxi, China from Chinese migrate workers. Clinical Trial Registration: ChiCTROPC17013106.